Melatonin promotes ripening of grape berry via increasing the levels of ABA, H(2)O(2), and particularly ethylene - Xu, Lili (Hortic Res, 2018)
The role of melatonin in the regulation of fruit ripening and the mechanism involved remain largely unknown. In “Moldova” grape berries, melatonin accumulated rapidly from onset of veraison, reached the maximum at 94 days after bloom (DAB) and then exhibited low levels at late stages of berry ripening. By contrast, abscisic acid (ABA) and hydrogen peroxide (H(2)O(2)) exhibited different accumulation patterns, and ethylene was primarily produced immediately before veraison. Further experiments demonstrated that 10 and particularly 100 µM melatonin treatments increased the levels of ABA, H(2)O(2), and ethylene production and promoted berry ripening compared with the control treatment, whereas 0.1 and 1.0 µM melatonin did not lead to clear effects. Additionally, the application of inhibitors indicated that ABA, H(2)O(2), and ethylene participated in the regulation of berry ripening induced by melatonin, and the suppression of ethylene biosynthesis produced the greatest inhibitory effects on melatonin-induced berry ripening compared with those of ABA and H(2)O(2). Melatonin also promoted ethylene production via ABA. In summary, 10 and particularly 100 µM melatonin treatments promoted berry ripening, which was accomplished, at least partially, via the other signaling molecules of ABA, H(2)O(2), and particularly ethylene. This research provides insight into melatonin signaling during berry ripening and may advance the application of melatonin to accelerate berry ripening.